2015
DOI: 10.2147/ppa.s81612
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of medication adherence among adults with type 2 diabetes mellitus in three Malaysian public health clinics: a cross-sectional study

Abstract: Medication adherence (MA) in adults with type 2 diabetes mellitus (T2D) is associated with improved disease control (glycated hemoglobin, blood pressure, and lipid profile), lower rates of death and diabetes-related complications, increased quality of life, and decreased health care resource utilization. However, there is a paucity of data on the effect of diabetes-related distress, depression, and health-related quality of life on MA. This study examined factors associated with MA in adults with T2D at the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 51 publications
4
52
1
2
Order By: Relevance
“…In the present study, there was a reduction in adherence to medication as the age of participants increased. This finding was in line with research in Malaysia, which showed that reduction of 1 year in the age of participants increased the probability of non-adherence to medication by 3.4% [27,28]; however, another study did not find any relationship between age and adherence to medication [29]. These differences can be explained in part by the different socioeconomic status of the studied population.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, there was a reduction in adherence to medication as the age of participants increased. This finding was in line with research in Malaysia, which showed that reduction of 1 year in the age of participants increased the probability of non-adherence to medication by 3.4% [27,28]; however, another study did not find any relationship between age and adherence to medication [29]. These differences can be explained in part by the different socioeconomic status of the studied population.…”
Section: Discussionsupporting
confidence: 90%
“…This finding was in line with the SHIELD study [30]. It is notable that one of the potential confounding factors might be the high prevalence of depression amongst obese people, which could lead to decrease in medication adherence [28,31]. Moreover, our findings indicated that the relationship between gender and adherence to medication was not significant.…”
Section: Discussionsupporting
confidence: 89%
“…While DiMatteo (DiMatteo, 2004) and Kirkman and colleagues (Kirkman et al, 2015) associated higher levels of education with medication adherence, a recent study by Chew and colleagues (Chew, Hassan, & Sherina, 2015) indicated that higher education was associated with poor diabetes medication adherence. Another review by Jin and colleagues (Jin, Sklar, Min Sen Oh, & Li, 2008) reported inconsistent findings.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, a large body of studies found that the above reported psychological factors are associated with sub-optimal glycemic control (Lustman et al, 2000), DM complications (de Groot et al, 2001), and decreasing levels of QoL (Chew et al, 2015). The combination of DM with negative mental health aspects, mainly depression and anxiety, is associated with an impaired QoL, as well as with a greater difficulty in patients to self-monitor their blood glucose levels (Lewko et al, 2012).…”
Section: Introductionmentioning
confidence: 99%